A novel Akt3 mutation associated with enhanced kinase activity and seizure susceptibility in mice - Shinichi Tokuda; Connie L. Mahaffey; B. Monks; Christian Faulkner; Morris J. Birnbaum; Steve C. Danzer; Wayne N. Frankel (2010)
In a phenotype-driven mutagenesis screen, a novel, dominant mouse mutation, Nmf350, caused low seizure threshold, sporadic tonic–clonic seizures, brain enlargement and ectopic neurons in the dentate hilus and molecular layer of the hippocampus. Genetic mapping implicated Akt3, one of four candidates within the critical interval. Sequencing analysis revealed that mutants have a missense mutation in Akt3 (encoding one of three AKT/protein kinase B molecules), leading to a non-synonymous amino acid substitution in the highly conserved protein kinase domain. Previous knockout studies showed that Akt3 is pivotal in postnatal brain development, including a smaller brain, although seizures were not observed. In contrast to Akt3Nmf350, we find that Akt3 null mice exhibit an elevated seizure threshold. An in vitro kinase assay revealed that Akt3Nmf350 confers higher enzymatic activity, suggesting that Akt3Nmf350 might enhance AKT signaling in the brain. In the dentate gyrus of Akt3Nmf350 homozygotes, we also observed a modest increase in immunoreactivity of phosphorylated ribosomal protein S6, an AKT pathway downstream target. Together these findings suggest that Akt3Nmf350 confers an increase of AKT3 activity in specific neuronal populations in the brain, and a unique dominant phenotype. Akt3Nmf350 mice provide a new tool for studying physiological roles of AKT signaling in the brain, and potentially novel mechanisms for epilepsy.